Sex worker affirmative therapy: conceptualization and case study. Issue 3 (3rd July 2019) - Bloomquist, Katie; Sprankle, Eric
Abstract: Prior research reported some segments of the sex worker population are at higher risks of negative health outcomes. Historically, these outcomes were viewed as a result of the work itself without taking into consideration the role of the stigma and often criminalization of the work that may be the contributing factors impacting distress. Therefore, drawing upon minority stress theory and affirmative therapy guidelines for the LGBT population, this article conceptualizes sex workers' mental health through a lens of stigma and stigma management. From this conceptualization, the article presents competency, assessment, and treatment principles to serve as the basis for sex worker affirmative therapy. A case study detailing a sex worker's struggles with boundary setting and establishing romantic relationships is presented to highlight how sex worker affirmative therapy can be applied in clinical practice.